Грошова оцінка земель у містобудівних системах на основі теоретичних засад - Кушнірук, Тетяна Миколаївна; Петрище, О. І. (НУБіП України, 2025)
Abstract: Due to the lack of a developed land and real estate market, there was a need to use non-market mechanisms to determine the price of land. The most important economic regulators of land relations include the normative monetary valuation of land plots, which is used to determine the amount of land tax, state duty on mining, inheritance and donation of land plots. Land rent, which is formed within urbanized areas, should be directed to financing the city’s infrastructure, that is, be used in the interests of each resident and ensure the rational use of land and the full functioning of the city economy as a whole.
Monetary valuation of land in urban planning systems based on theoretical principles
Keywords: грошова оцінка землі; ринок землі; населені пункти; monetary value of land; land market; settlements